106 DISASSOCIATION BETWEEN PHYSICIAN KNOWLEDGE AND PRACTICE IN TREATMENT OF DYSLIPIDEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS. (1st January 2005) - Sarwal-Gyani, A.; Hanley, J.
Abstract : Objective: The appreciation that cardiovascular disease represents the major morbidity and mortality in type 2 diabetes mellitus has resulted in a sea change in the approach to the treatment of the diabetic patient. A renewed emphasis has been placed on modifying cardiovascular risk factors to include aggressive management of dyslipidemia. It is unclear whether primary care physicians (PCPs) are knowledgeable about these concepts and translate it into their care. To assess the physician's knowledge and practice, we surveyed all physicians practicing in a community health center (CHC) and reviewed a sample of their patients' charts for compliance. Methods: 1. A short survey targeting physicians in the (CHC) as well as some in the community focusing on their knowledge and understanding of the cardiovascular risk of diabetes mellitus type 2. 2. Chart review of patients in the CHC, focusing on the presence and treatment of dyslipidemia and the number of patients that reached goal. Results: 1. Of 17 PCPs surveyed within the CHC, 13 answered that they treat their patients to the NCEP ATP III recommended goals of HDL; all 17 answered that they treat their diabetics to the LDL goal and triglyceride goal. Of 14 PCPs surveyed within the community, only 3 answered that they treat their patients to all of the recommended goals. 2. Of 75 diabetic charts reviewed, 65 had dyslipidemia. Of these 65 patients, 48 had high LDL, 17 had low HDL, 47 had high triglycerides. Of the 48 patients with high LDL, 17 were treated and 3 were treated to goal (TTG). Of the 17 patients with low HDL, 10 were treated and 3 were TTG. Of the 47 patients with high triglyceride, 24 were treated and 4 were TTG. Conclusions: The results of our short survey showed that most of physicians in the CHC had an appropriate understanding of the need to treat dyslipidemia, as well as the goals in the diabetic patient. Unfortunately, this was not translated into the optimum care. It is not clear what the barrier is to achieving better care. Certainly, many of the patients who are cared for are indigent and cannot afford many medications; however, many of these medications are available through a program. Of further concern is that the PCPs outside CHC were unable to identify even the goals of therapy.